2018
DOI: 10.3389/fnmol.2018.00028
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Expression of Serotonin Receptor 5b Alters Breathing Behavior in Male MeCP2 Knockout Mice

Abstract: Mutations in the transcription factor methyl-CpG-binding protein 2 (MeCP2) cause the neurodevelopmental disorder Rett syndrome (RTT). Besides many other neurological problems, RTT patients show irregular breathing with recurrent apneas or breath-holdings. MeCP2-deficient mice, which recapitulate this breathing phenotype, show a dysregulated, persistent expression of G-protein-coupled serotonin receptor 5-ht5b (Htr5b) in the brainstem. To investigate whether the persistence of 5-ht5b expression is contributing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…In summary, undoubtedly UWBP allows to determine parameters of respiratory rhythm, respiratory rate as well as parameters that define regularity of the respiratory rhythm an also phases of respiratory arrest (Hulsmann et al ., 2016; Vogelgesang et al ., 2017; Mesuret et al ., 2018; Vogelgesang et al ., 2018). However, for defining tidal volume, UWBP is a weak method.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, undoubtedly UWBP allows to determine parameters of respiratory rhythm, respiratory rate as well as parameters that define regularity of the respiratory rhythm an also phases of respiratory arrest (Hulsmann et al ., 2016; Vogelgesang et al ., 2017; Mesuret et al ., 2018; Vogelgesang et al ., 2018). However, for defining tidal volume, UWBP is a weak method.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, selective agonist or antagonist are still no available for 5-HT 5B . Therefore, up to now, a very limited number of studies were conducted to address the function of 5-ht 5b in CNS ( Maekawa et al, 2010 ; Vogelgesang et al, 2017 , 2018 ; Niebert et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are only two studies that report the possible roles of 5-ht 5b in the regulation of animal behavior. 5-HT5B has been found to be dramatically upregulated in mice undergoing social stress ( Maekawa et al, 2010 ) and in mouse models of Rett syndrome (RTT) ( Vogelgesang et al, 2018 ; Niebert et al, 2017 ), a severe neurodevelopmental disorder caused by mutations in the transcription factor MeCP2. The role of 5-HT5B in the brain remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ure et al also demonstrated that restoration of MECP2 gene in GABAergic neurons in RTT mouse models caused the improvement of multiple RTT‐like phenotypes: respiratory anomalies however were not included, suggesting an interplay of multiple factors at the basis of normal respiration (Ure et al, 2016). It is not fully understood which are the causes related to abnormal breathing in RTT, but studies suggest the involvement of norepinephrine (Viemari et al, 2005), neurotrophic factors like BDNF (Li & Pozzo‐Miller, 2014), dysregulation of expression of 5‐ht5b‐receptors (Vogelgesang, Niebert, Bischoff, Hülsmann, & Manzke, 2018) or decrease in excitatory synaptic connectivity in several parts of brain cortex, including the medial prefrontal cortex (Sceniak et al, 2016). Studies on MECP2 ‐null mice show also an altered sensitivity to blood gases: increased hypoxia susceptibility associated with failure to increase ventilation in presence of moderate hypercapnia (Jiang, Cui, Zhong, Johnson, & Wu, 2017).…”
Section: Introductionmentioning
confidence: 99%